ANALISIS TINGKAT PERTUMBUHAN DAN PEMBANGUNAN PEREKONOMIAN UNTUK KESEJAHTERAAN MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM ( Daerah Lampung Utara ) - Ikhwan Udin; Muhammad Iqbal Fasa; Prof Suharto (Fakultas Ekonomi Universitas Bangka Belitung, 2021)
Abstract Economic growth not only pursues good in the world alone but also (even the ultimate) good in the afterlife. Economic growth is seen as the most important part of economic policy in any country or system. As economic growth is one indicator of increasing public welfare. The study aims to know how economic growth and economic development affect people's welfare according to the islamic economic perspective. The study USES the quantitative method and the type of data used to make it out of the province of lampung and BPS district of north lampung. The type of data we're using is a time series of 2011-2016. The results of this study show that economic growth has hada negative and significant impact on the human development index. According to the islamic economic perspective, economic growth is multidimensional, which includes quantitative and qualitative aspects. His purpose is not merely the welfare of the world's material, but also the eternal agony. Keywords: economic growth, economic development, civic prosperity and the islamic economy